Yasak Bir Hafızayla Yüzleşmek: Menemen Olayı İrtica mı, Komplo mu ? - Öz, Eyüp (FSM Vakıf Üniversitesi, 2015)
1930 yılı Türkiye için birkaç nedenle gerçek dönüm noktalarından biri olarak tanımlanabilir. Kemalist iktidarın radikal dini reformları ve ekonomik krizin toplumsal hoşnutsuzluğu derinleştirmesi, ülkeyi iki temel noktada değişime zorlamıştır: Ekonomide devletçilik ve çoğulcu politik sistem. Bizzat Mustafa Kemal Atatürk’ün emriyle kurulan Serbest Cumhuriyet Fırkası, sözkonusu iki temel yönelimin bir arada yürütülmesini öngören siyaset mühendisliği ürünü olarak, 12 Ağustos’ta tarih sahnesindeki yerini aldı. Serbest Fırka 17 Kasım’da aniden feshedilmesine rağmen parti tabanı aylar boyunca varlığını sürdürecektir. Toplumsal muhalefetin sindirilmesi, sıradışı mehdici bir isyana verilen orantısız cevaba rağmen mümkün olmamıştır. Bu makalede, 23 Aralık 1930’da meydana gelen Menemen Olayı uhrevi kurtuluş hareketleri perspektifinde ele alınıyor.

For several reasons, the year 1930 can be defined as a genuine turning point for the history of modern Turkey. The radical religious reforms under the Kemalist leadership and thegrowing social discontent due to the Economic Crisis forced the country to go through a transformation towards two essential directions: economic statism and pluralistic political system. Created on the personal order of Mustafa Kemal, the Liberal Republican Party took its place in the historical scene on August 12th, as a pure product of the political engineering which was envisaging the simultaneous implementing of this double orientation. Though the Liberal Party was unexpectedly dissolved, its electorate continued to exist for several more months. The disproportionate response to a singular messianic uprising did not succeed in the suppressing of social protests. Born in Magnesia and ended in Menemen on December 23rd, 1930, this insurrectionary wave has shaken the power profoundly, with the murder of a sub-lieutenant.
To Confront with a Forbidden Memory: Is the Menemen Incident a Reaction or a Conspiracy ?
Keywords: Ekonomik kriz; Serbest Cumhuriyet Fırkası; Menemen olayı; Mehdici isyan; Economic crisis; Liberal Republican Party; Menemen incident; Messianic uprising